Factors affecting activation and utilization of carbon dioxide in cyclic carbonates synthesis over Cu and Mn peraza macrocyclic complexes - Srivastava, R.; Bennur, T. H.; Srinivas, D. (Journal of Molecular Catalysis A - Chemical, 2005)
The catalytic activities of several Cu and Mn aza complexes for cyclic carbonate synthesis from CO2 and epoxides are reported. The various factors affecting activation of CO2 by metal complexes and its utilization in cyclic carbonate synthesis have been investigated. Fr-IR, UV-vis and EPR spectroscopic investigations reveal that CO2 coordinates to Cu in eta(1)-C mode of coordination. Nature of the ligand and substitution influence the lability of metal-CO2 bonding. The differences in the catalytic activities are correlated with the mode and strength of CO2 binding. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: benign synthesis; Carbon dioxide; catalysis by Cu and Mn complexes; CO2 activation; CO2 fixation; CO2 utilization; cyclic carbonates; polycarbonates; spectroscopy

Keggin ion mediated synthesis of hydrophobized pd nanoparticles for multifunctional catalysis - Mandal, Sujata; Das, Amitava; Srivastava, R.; Sastry, M. (Langmuir, 2005)
Development of simple and reliable protocols for the synthesis of organically soluble catalytically active metal nanoparticles is an important aspect of research in nanomaterials. We demonstrate herein the formation of Pd nanoparticles by reduction of aqueous Pd(NO3)(2) by photoexcited Keggin ions (phosphotungstate anions). This results in the formation of Pd nanoparticles capped with with Keggin ions that render the particles negatively charged. The Keggin ion capped Pd nanoparticles may then be phase transferred into nonpolar organic solvents such as toluene by electrostatic complexation with cationic surfactants such as octadecylamine at the liquid-liquid interface. This results in a new class of catalyst wherein both the Pd core and Keggin ion shell may be used in a range of catalytic reactions leading to a truly multifunctional catalyst dispersible in organic solvents.

Fe-Zn double-metal cyanide complexes as novel, solid transesteritication catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Journal of Catalysis, 2006)
Fe-Zn double-metal cyanide complexes are currently used as catalysts for the ring-opening polymerization of epoxides, as well as the coupling of epoxides and CO2 for the production of polycarbonates. We report their novel application as highly efficient solid catalysts for the transesterification reactions of carbonates. The catalysts were prepared from aqueous solutions of ZnCl2 and K4Fe(CN)(6) in the presence of tert-butanol (complexing agent) and tri-block copolymer EO20PO70EO20 (average molecular weight, 5800; co-complexing agent). They were characterized by chemical analysis, XRD, thermal analysis, N-2 adsorption, magnetic susceptibility, SEM, and FTIR, diffuse reflectance UV-visible, EPR, and X-ray photoelectron spectroscopies. Their acidity was determined from the IR spectra of adsorbed pyridine and the temperature-programmed desorption of NH3. Catalyst samples prepared with both complexing and co-complexing agents were found to be more acidic and catalytically active than those prepared without these agents. These catalysts are more active/selective than other solid catalysts hitherto reported. Dimethyl carbonate, for example, could be synthesized with 100% selectivity and an isolated yield of >86% by the reaction of propene carbonate with methanol. The catalysts can be recycled without significant loss in activity. Lewis acidic Zn ions are the possible active sites for the transesterification reaction. (c) 2006 Published by Elsevier Inc.
Keywords: cyclic carbonate; Dimethyl carbonate; double metal cyanide Fe-Zn complexes; organic carbonate; transesterification catalyst

Hydrophobic, solid acid catalysts for production of biofuels and lubricants - Sreeprasanth, Pulinthanathu Sree; Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2006)
A novel application of Fe-Zn double-metal cyanide (DMC) complexes as solid catalysts in the preparation of fatty acid alkyl esters (biodiesel/biolubricants) from vegetable oils is reported. The catalysts are hydrophobic (no H2O adsorption at reaction temperatures) and contain only Lewis acidic sites (NH3 and pyridine adsorption). Bronsted acid sites are absent (absence of 1546 and 1639 cm(-1) bands on adsorption of pyridine). Basic sites are also absent (no CO2 adsorption). Unlike the homogeneous or other solid catalysts (like ZnO-Al2O3, for example), the Fe-Zn, DMC catalysts are highly active even for the simultaneous transesterification of triglycerides and esterification of the free fatty acids (FFA) present in unrefined and waste cooking oils as well as non-edible oils. They are also tolerant of water, probably, due to their surface hydrophobicity. A relationship between the transesterification activity and the concentration of strong Lewis acid sites has been observed. Coordinatively unsaturated Zn2+ ions in the structure of the Fe-Zn complex are the probable active sites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alcoholysis of vegetable oils; Biodiesel; Biolubricants; double-metal cyanides (DMC); esterification of free fatty acids; fatty acid alkyl esters; fatty acid methyl esters; solid Fe-Zn catalysts; transesterification of vegetable oils

Sites for CO2 activation over amine-functionalized mesoporous Ti(Al)-SBA-15 catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2006)
{Activation of CO and its utilization in the synthesis of chloropropene and styrene carbonates over functionalized, mesoporous SBA-15 solids, have been investigated. The surface basicity of SBA-15 was modified with nitrogen-based organic molecules of varying basicity viz., alkyl amines (-NH2), adenine (Ade), imidazole (Im) and guanine (Gua). The surface of SBA-15 was also functionalized with Ti4+ and Al3+ species. The acid-base properties of these modified SBA-15 materials were investigated by temperature-programmed desorption (TPD) and diffuse-reflectance infrared Fourier transform (DRIFT) spectroscopy. NH3 and pyridine were used as probe molecules for acid sites, while CO, was used to characterize the basic sites. CO was activated at the basic amine sites forming surface carbamate species (IR peaks: 1609 and 1446 cm(-1)). The latter reacted further with epoxides adsorbed on the acid sites forming cyclic carbonates. A correlation between the intensity of the IR peak at 1609 cm(-1) and cyclic carbonate yield has been observed. The cyclic carbonate yields were higher when both the acid and base functionalities were present on the surface. The Ti- and Al-SBA-15 functionalized with adenine exhibited the highest catalytic activity and selectivity. There is an optimal dependence (''
Keywords: aromatization; Ga-based zeolites; propane; Si/Al ratio; Si/Ga ratio; zeolitic factors

Syntheses of polycarbonate and polyurethane precursors utilizing CO2 over highly efficient, solid as-synthesized MCM-41 catalyst - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Tetrahedron Letters, 2006)
As-synthesized MCM-41 was used as a reusable, heterogeneous catalyst for the eco-friendly synthesis of cyclic carbonate precursors of polycarbonates via a cycloaddition reaction of CO2 with epoxides. This catalyst is also efficient for the synthesis of alkyl and aryl carbamate precursors of polyurethanes via the reaction of amines, CO2 and alkyl halides. Both these reactions were carried out under mild conditions and without using any solvent or co-catalyst. CO2 is utilized as a raw material replacement for toxic phosgene in the conventional synthesis of these chemicals. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: carbamates; carbon dioxide utilization; CO2 fixation; cyclic carbonates; eco-friendly processes; MCM-41; polycarbonates; polyurethanes

Novel method for the protection of amino alcohols and carbonyl compounds over a heterogeneous, reusable catalyst - Srivastava, P.; Srivastava, R. (Catalysis Communications, 2008)
A novel application of Al-SBA-15 catalyst in the protection of amino alcohols and carbonyl compounds is reported. N-t-butoxy carbonyl [N(Boc)] amino alcohols were protected using 2,2-dimethoxyproparic (DMP) to form acetonides. Acetonide deprotection was also studied using the same catalyst to obtain the parent amino alcohol. Protection of carbonyl compounds was Studied using neopentyl glycol, ethylene glycol and propylene glycol as the protecting agents. A series of commercially important molecules Such as 2-substituted and 2,2-disubstituted 1,3-benzodioxoles were synthesized by reacting carbonyl compounds with catechol. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Acetalization; acetonide; Amino alcohol; benzodioxole; protection